LIM-Only Protein FHL2 Is a Negative Regulator of Transforming Growth Factor β1 Expression - Dahan, Jennifer (Mol Cell Biol, 2017)
Transforming growth factor β1 (TGF-β1) is a master cytokine in many biological processes, including tissue homeostasis, epithelial-to-mesenchymal transition, and wound repair. Here, we report that four and a half LIM-only protein 2 (FHL2) is a critical regulator of TGF-β1 expression. Devoid of a DNA-binding domain, FHL2 is a transcriptional cofactor that plays the role of coactivator or corepressor, depending on the cell and promoter contexts. We detected association of FHL2 with the TGF-β1 promoter, which showed higher activity in Fhl2(−/−) cells than in wild-type (WT) cells in a reporter assay. Overexpression of FHL2 abrogates the activation of the TGF-β1 promoter, whereas the upregulation of TGF-β1 gene transcription correlates with reduced occupancy of FHL2 on the promoter. Moreover, ablation of FHL2 facilitates recruitment of RNA polymerase II on the TGF-β1 promoter, suggesting that FHL2 may be involved in chromatin remodeling in the control of TGF-β1 gene transcription. Enhanced expression of TGF-β1 mRNA and cytokine was evidenced in the livers of Fhl2(−/−) mice. We tested the in vivo impact of Fhl2 loss on hepatic fibrogenesis that involves TGF-β1 activation. Fhl2(−/−) mice developed more severe fibrosis than their WT counterparts. These results demonstrate the repressive function of FHL2 on TGF-β1 expression and contribute to the understanding of the TGF-β-mediated fibrogenic response.